Reconstruction of Tumor-Induced Pelvic Defects With Customized, Three-Dimensional Printed Prostheses - Xu, Shenglin; Guo, Zehao; Shen, Qiling; Peng, Yongjun; Li, Jian; Li, Sheng; He, Peng; Jiang, Zheng; Que, Yukang; Cao, Kun; Hu, Bo; Hu, Yong (Frontiers in Oncology, 2022)
Background Reconstruction of pelvis girdle stability after tumor-induced hemipelvectomy remains challenging. We surgically treated 13 patients with custom-made, three-dimensional printed hemipelvic prostheses. We aim to identify the preliminary outcomes for patients who have been managed with more mixed regions of prosthetic pelvic reconstruction and the feasibility of two reconstructive systems. Methods 7 males and 6 females treated at our center between January 2019 and May 2021 were included. There were 11 primary sarcomas and 2 solitary bone metastases. After en-bloc tumor resection, two types of personalized, three-dimensional printed prostheses were fixed to restore the stability and rebuild the load transfer. The position of the reconstructed hemipelvis was evaluated on anteroposterior plain radiograph. The complications and outcomes were traced. Histological analysis at the porous structure were discovered in one amputation specimen. Results The operative duration was 467 ± 144 mins and the blood loss was 3119 ± 662 ml. During a follow-up of 22.4 ± 8.5 months, two patients had delayed wound healing and one had a second stage flap transfer. One patient with osteosarcoma died of pulmonary metastasis 27 months after surgery. Two patients with marginal resection suffered from local recurrence and had extra surgeries. One patient had traumatic hip dislocation 2 months after surgery and manipulative reduction was performed. The acetabular inclination of the affected side was 42.2 ± 4.3°, compared with 42.1 ± 3.9° on the contralateral side. The horizontal distance between the center of the femoral head and the middle vertical line was 10.4 ± 0.6 cm, while the reconstructed side was 9.8 ± 0.8 cm. No significant difference in acetabular position after surgery was found (P > 0.05). The amputation specimen harvested from one patient with local recurrence demonstrated bone and soft tissue ingrowth within the three-dimensional printed trabecular structure. Walking ability was preserved in all patients who are still alive and no prosthesis-related complications occurred. The MSTS score was 22.0 ± 3.7. Conclusions Both types of custom-made, three-dimensional printed prostheses manifested excellent precision, mechanical stability and promising functional rehabilitation. The porous structure exhibited favorable histocompatibility to facilitate the ingrowth of bone and soft tissue.